Grassroots Projects as a model for the globalization of Central Asian traditional music and as a subject of research - Jumaniyazova, R.K. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article is devoted to the substantiation of a new subject of modern culture study. In the article the concept of Grassroots Projects as a cultural phenomenon is discussed that is widespread in America and involves projects initiated by musicians without the support of the state or large institutions. Such projects are now becoming one of the most effective and high-quality examples of the globalization of Central Asian traditional music. The obvious novelty and relevance of the article is connected with the emerging new perspectives for musicians and researchers of Kazakhstan. The possibility of the existence of certain and new musical groups on their own terms, without government funding, allows to implement of independent projects at the expense of the community of professionals and music lovers. It is important that such Grassroots Projects should have value for the community, which can unite representatives of different countries and social strata. Globalization processes are an objective and unavoidable reality, they can contribute to the development and prosperity of national cultures. The interchange of cultural and scientific values is a part of natural evolution. The difference between American and Kazakhstani musicology is indicated which is manifested both in research methodology and in the direct connection between science and practice. In conclusion, the existence of all the conditions for the initiation and development of Grassroots Projects in Kazakhstan is indicated. It is also proposed to develop Grassroots Projects within the framework concert and performing practice of Kazakhstan, initiating joint concert programs. The importance of studying the phenomenon of Grassroots Projects and introduction of the experience of such projects into modern practice is emphasized.
Grassroots Projects Орталық Азиядағы дəстүрлі музыка жаһандануының үлгісі жəне зерттеу тақырыбы ретінде
Grassroots Projects как модель глобализации и предмет исследования традиционной музыки в Центральной Азии
Keywords: traditional music; Grassroots Projects; musicology; globalization; Kazakh music; cultural tolerance